Earthworm Cultivation (Lumbricus rubellus) Using Cattle Manure Waste in Pangalengan District, Bandung Regency - Aryanto, Arie; Alifiyah, Na'ilah Insani; Zikriyani, Hikmah (ORGANISMS: JOURNAL OF BIOSCIENCES, 2025)
This high level of organic waste poses significant environmental risks if left unmanaged. Therefore, there is a need for waste management strategies that are simple, cost-effective, and environmentally sustainable. One such approach is vermiculture the cultivation of earthworms to convert organic waste into nutrient-rich vermicompost. Integrating Effective Microorganisms (EM4) and tomato waste into cattle manure feed has the potential to enhance nutrient bioavailability through microbial fermentation, which in turn supports earthworm metabolism and growth. This study aims to evaluate the productivity of Lumbricus rubellus and the efficiency of vermicompost production under different feed formulations. The experiment was conducted using a completely randomized design (CRD) with four feed treatments: cow manure (P1), cow manure + EM4 (P2), cow manure + tomato waste (P3), and cow manure + tomato waste + EM4 (P4), with three replications per treatment. The observed parameters included earthworm weight, earthworm length, vermicompost production, and proximate analysis of earthworm biomass. This study also assesses the impact of these feed combinations on the growth performance of L. rubellus and the resulting vermicompost yield, within the agroclimatic conditions of Pangalengan. Additionally, the nutritional composition of the harvested earthworm biomass is evaluated to explore its potential as a supplementary protein source for livestock feed contributing to sustainable and circular agricultural practices in dairy farming systems.